2017
DOI: 10.1063/1.4983325
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gas dilution on the nanoparticles nucleation in a low pressure capacitively coupled acetylene discharge

Abstract: The effects of gas dilution on the chemistry of macromolecules and nucleation of nanoparticles in a low pressure radio-frequency acetylene discharge are investigated by employing a self-consistent, one dimensional multi-fluid model. Ar, He, and H2 are used for the dilution with different percentages, keeping the total gas inlet constant. The results of numerical simulations showed that the nucleation rate decreases monotonically with H2 fraction, when the plasma is diluted in hydrogen. But, for Ar and He dilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…The experiments also revealed that the formation of dust particles in Ar/C 2 H 2 plasmas is accompanied by a decrease of the electron and acetylene densities and by an increase of the electron temperature and the density of metastable argon atoms . Numerical simulations of the nucleation of nanoparticles in C 2 H 2 and Ar/C 2 H 2 plasmas showed that positive and negative ions, as well as hydrocarbon radicals, may take part in the initial stage of particle formation …”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…The experiments also revealed that the formation of dust particles in Ar/C 2 H 2 plasmas is accompanied by a decrease of the electron and acetylene densities and by an increase of the electron temperature and the density of metastable argon atoms . Numerical simulations of the nucleation of nanoparticles in C 2 H 2 and Ar/C 2 H 2 plasmas showed that positive and negative ions, as well as hydrocarbon radicals, may take part in the initial stage of particle formation …”
Section: Introductionmentioning
confidence: 94%
“…We also assume that the plasma contains negative ions C 2 H − with density n − although not measured in our experiment due to mass spectrometer limitations and complexity in extracting negative ions from the positive plasma glow. At large ratio of the argon atom density to that of acetylene molecules, the anions C 2 H − are the dominant negative ions …”
Section: The Modelmentioning
confidence: 99%
See 3 more Smart Citations